Clinical Characteristics and Factors Associated With Hypertension in 205 Hospitalized Children: A Single-Center Study in Southwest China - Yang, Zhiyong; Huang, Yanyun; Qin, Yan; Pang, Yusheng (Frontiers in Pediatrics, 2021)
Objective: The aim of this study was to investigate the clinical characteristics and factors associated with pediatric hypertension and target organ damage (TOD). Methods: We retrospectively reviewed clinical data from 205 children with hypertension treated in our hospital from 2007 to 2018. The patients were classified based on the type of hypertension (primary, secondary) and presence of TOD (heart, brain, retina). Logistic regression was performed to identify the factors independently associated with hypertension and TOD. Results: There were 107 males, 97 females, and one intersex in this study, with an age range of 0.1–17.9 years. Majority of cases (177, 86.3%) had secondary hypertension, while 13.7% had primary hypertension. The most frequent cause of secondary hypertension was renal disease (59.32%). Elevated serum creatinine level (odds ratio [OR]=7.22, 95% confidence interval [95%CI]=1.6–32.62, P=0.01), blood urea nitrogen (OR=6.33, 95%CI=1.81–22.19, P=0.004), serum uric acid level (OR=3.66, 95%CI=1.20–11.22, P=0.023), and albuminuria (OR=3.72, 95%CI=1.50–9.26, P=0.005) were independently associated with secondary hypertension. Elevated serum uric acid and blood urea nitrogen levels were associated with left ventricular hypertrophy (OR=6.638, 95%CI=1.349–32.657, P=0.02) and hypertensive encephalopathy (OR=4.384, 95%CI=1.148–16.746, P=0.031), respectively. Triglyceride level correlated with hypertensive retinopathy (P=0.001). Conclusion: Pediatric hypertension was most often secondary, with renal disease as the leading cause. Elevated levels of serum uric acid, blood urea nitrogen, serum creatinine, and albuminuria may indicate secondary hypertension in childhood. Elevated serum uric acid, blood urea nitrogen, and triglyceride levels were associated with left ventricular hypertrophy, hypertensive encephalopathy, and hypertensive retinopathy, respectively.